Adsorption of Copper and Iron Using Low Cost Material as Adsorbent - Tariq S. Najim; Nazik J. Elais; Alya A. Dawood (E-Journal of Chemistry)
In this study, pine fruit was used as solid adsorbent for removal of ferrous and copper ions from aqueous solutions through batch equilibrium technique. The influence of contact time, pH of the solution and initial concentration of metal ions on adsorbed amount of metal ions were investigated. 90 minutes of adsorption time was found sufficient to reach equilibrium for ferrous ion and 120 minutes for copper ion. Adsorption of metal ions were pH dependent and the results indicate the optimum pH for the removal of Fe+2 was found to be 5.0 and that of Cu+2 was 7.0, the highest adsorption capacity was found to be 4.8 and 14.1 mg of metal ion per gram of adsorbent at initial concentration of 22.22 mg/L and 57.6 mg/L of ferrous and copper ions respectively and would be higher with higher initial concentration. Ferrous ion was removed by 96.3 - 97.3% and copper ion by 94.1-96% along the whole range of initial concentrations. Isotherm studies showed that the data were best fitted to the Freundlich isotherm model. The kinetic data corresponded well with the pseudo-second order equation, suggesting that the adsorption process is presumably a chemisorption.